Tourism and active recreation as elements of seniors’ lifestyle - Hołowiecka, Beata; Grzelak-Kostulska, Elżbieta (Acta Universitatis Lodziensis. Folia Oeconomica, 2013)
This article deals with the relationships between seniors' lifestyles and their health and quality of life with respect to the determinants and consequences of aging. As found, considering the complex and dynamically changing set of factors determining individuals' lifestyles the elderly "withdraw from life" too early and too far. This worrying finding brings into attention active recreation as an approach allowing people to maintain physical fitness, mental health and social activity, and thus being capable of postponing the most severe effects of aging. Before presenting the potential of active tourism as a useful instrument of active recreation, the social consequences of aging and the special character of "seniors" as a social group are discussed in terms of what enables and what restricts the use of free time. This provides a background for showing the functions of tourism as an activity having a beneficial effect not only on physical and mental health, but also on the social interaction of elderly people. Active recreation effectively compensates for losses caused by economic inactivity and withdrawal from certain social roles by building various social relations (including intergenerational) and breaking isolation, as well as by initiating a learning process based on new experiences and contacts, and developing interests and skills that strengthen the feeling of independence, self-confidence and self-esteem. Active tourism, adjusted to the needs and capabilities of elderly people, may make a measurable contribution to better quality of their lives.